2020
DOI: 10.1016/j.drudis.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The political economics of cancer drug discovery and pricing

Abstract: Highlights Despite falling age-specific mortality rates cancers are causing a rising proportion of all deaths. Anticancer medicines now cost 0.1−0.2% of the typical OECD country’s GDP. Although complex, imperfect and politicised, markets for innovative medicines are delivering important benefits. Without enhanced risk sharing and value based pricing the intellectual property laws facilitating much drug discovery may become politically un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…This price is often the result of R&D costs plus a margin to ensure an acceptable level of profitability for the manufacturers 13 . Even a small improvement in survival time gives laboratories enough leverage to demand astronomical prices even when the drugs have not required significant investment in research and development 14 .The NCCP policy of reducing purchase prices by 50% has certainly reduced them considerably. However, it was reported that they remain well above the prices of private pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…This price is often the result of R&D costs plus a margin to ensure an acceptable level of profitability for the manufacturers 13 . Even a small improvement in survival time gives laboratories enough leverage to demand astronomical prices even when the drugs have not required significant investment in research and development 14 .The NCCP policy of reducing purchase prices by 50% has certainly reduced them considerably. However, it was reported that they remain well above the prices of private pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…The study cut-off date was selected to provide sufficient follow-up time to track indication approvals after the initial approval. The scope of the study was restricted to multi-indication medicines used in oncology, a therapeutic area that is a) of high interest to decision-makers given burden of disease, high treatment costs and challenges in evidence development [ 14 ] and b) increasingly subject to follow-on indication [ 1 ]. The study scope is also restricted to multi-indication monotherapy treatments to limit the impact of combination therapies.…”
Section: Methodsmentioning
confidence: 99%
“…A primary aim of pharmaceutical policy is to promote timely, equitable, affordable and sustainable access to effective medicines [9]. Policy makers must balance the shortterm goal of promoting widespread access to currently available treatment with long-term global R&D priorities and the need to develop further treatments for diseases with unmet need [26]. Value-based pricing, or ensuring the price paid for a medicine reflects the value it provides, falls at the intersection of these two objectives.…”
Section: Barriers To Implementa On Of Ibpmentioning
confidence: 99%